Role of bone marrow aspiration and biopsy in elaborating the diagnosis of pancytopenia - Dr. Rajesh H Chandan; Dr. Sujata S Giriyan (Tropical Journal of Pathology and Microbiology, 2018)
Background and Aims: Pancytopenia may be a manifestation of a wide variety of disorders which primarily or secondarily affects the bone marrow. Bone marrow failure syndromes and malignancies are serious and lifethreatening causes, but certain non-malignant conditions such as infection, and nutritional anemia are equally important. The severity of pancytopenia and the underlying pathology determine the implementation of correct management and prognosis. Materials and Methods: This was a prospective study conducted for a period of two years on 134 patients of pancytopenia. Detailed history, thorough clinical examination, complete hemogram, peripheral smear examination, reticulocyte count evaluation and bone marrow aspiration was performed in all cases. In addition, trephine biopsy was done in the same setting wherever indicated. Results: The age ranged from 15 to 75 years with a mean age of 30.9 years. The most common cause of pancytopenia was Megaloblastic anemia (37%) followed by Nutritional anemia (31%), aplastic anemia (9%) and Leukemia (1.75%). Majority (79%) of the patients had hyper cellular bone marrow followed by hypocellular (13%) and normal cellular marrow (8%). Conclusion: Elaborate hematological investigations and bone marrow examination, both, in correlation with clinical findings are vital for the diagnosis of pancytopenia. Bone marrow Aspiration and Trephine biopsy, complement each other in diagnosis of challenging cases.